Therapy of Pediatric-Onset Multiple Sclerosis: State of the Art, Challenges, and Opportunities - Margoni, Monica; Rinaldi, Francesca; Perini, Paola; Gallo, Paolo (Frontiers in Neurology, 2021)
Treatment of paediatric-onset multiple sclerosis (POMS) has been tailored after observational studies and data obtained from clinical trials in adult multiple sclerosis patients (AOMS). There are an increasing number of new therapeutic agents for AOMS, and many will be formally studied for use also in POMS. However, there are important efficacy and safety concerns regarding the use of these therapies in children and young adults. This review will discuss the current state of the art of POMS therapy and will focus on the newer therapies (oral and infusion disease modifying drugs) and on those still currently under investigation.